2020
DOI: 10.1109/access.2020.2973006
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Infections Using Computational Intelligence – A Systematic Review

Abstract: Infections encompass a set of medical conditions of very diverse kinds that can pose a significant risk to health, and even death. As with many other diseases, early diagnosis can help to provide patients with proper care to minimize the damage produced by the disease, or to isolate them to avoid the risk of spread. In this context, computational intelligence can be useful to predict the risk of infection in patients, raising early alarms that can aid medical teams to respond as quick as possible. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 99 publications
0
21
0
Order By: Relevance
“…Compared with other types of cancer, there is less study on class imbalance methods for lung cancer. Few research es als o classified the Lung nodules [83,84], chest-related diseases [85,86], identification of thoracic diseases [87], forecasting of COVID-19 [84,88,89].…”
Section: Application Of Class Imbalance M Ethods To Cancer Datasetsmentioning
confidence: 99%
“…Compared with other types of cancer, there is less study on class imbalance methods for lung cancer. Few research es als o classified the Lung nodules [83,84], chest-related diseases [85,86], identification of thoracic diseases [87], forecasting of COVID-19 [84,88,89].…”
Section: Application Of Class Imbalance M Ethods To Cancer Datasetsmentioning
confidence: 99%
“…Regarding Computational Intelligence applications, Baldominos et al [1] performed a systematic literature review aiming to find studies that adopted computational intelligence to predict infections in patients using physiological data as features. The study analyzed 101 relevant documents between the period of 2003 and 2019, showed that automatic diagnosis of these diseases is well documented in medical literature and concluded that sepsis, Clostridium difficile infection and surgical site infections were the most addressed.…”
Section: Background and Related Workmentioning
confidence: 99%
“…According to Baldominus et al [1], infectious diseases are the result of the invasive action of microscopic organisms (e.g., bacteria or viruses) in the body, and may be presented in many different types with different effect ranges. For example, while some infected bodies can remain asymptomatic, others can reach high risks of death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is becoming increasingly difficult to ignore the growth of an aging population in Europe, since a 74% rise in the population aged over 65 is expected by 2060 [1], [2]. This group of people have high rates of comorbidity [3], causing a very high consumption of resources in terms of both primary and specialised care [4].…”
Section: Introductionmentioning
confidence: 99%